Indonesian EFL Teacher’s Ideologies of Lingua Culture - Morganna, Ruly (ENGLISH FRANCA : Academic Journal of English Language and Education, 2019)
This study aimed at investigating the interpretation of lingua-culture and its depiction in EFL learning based on Indonesian EFL teachers’ ideologies. This study used an instrumental case study that purposefully engaged ten Indonesian EFL teachers as the participants. A semi-structured interview was assigned to garner the expected data. This study revealed that eight teachers, ones holding an essentialist ideology, interpreted lingua-culture as one language with one culture and depicted it into several characteristics including becoming native-like English users as the goal, using natively authentic materials, framing communicative competence theory for use, and applying indirect cultural teaching. On the contrary, the rest two teachers, ones adhering to a non-essentialist ideology, interpreted lingua-culture as one language with multiple cultures and depicted it into some characteristics extending to becoming intercultural English users as the goal, using cross-cultural non-native English materials, framing intercultural communicative competence for use, and executing direct cultural teaching. As the implication, anchored in the nature of multiculturality of Indonesian students, this study promotes EFL teachers to hold the non-essentialist ideology for its sustainability. This study offers two conceptual frameworks vis-a-vis EFL lingua-culture ideologies. Of the two, there is only one scientifically considered ideal to fit the multiculturality of Indonesian students. Keywords -EFL learning ideology, lingua-culture, multiculturality